ANALISIS KELEMBAGAAN TERHADAP PELAKSANAAN PROGRAM DEVERSIFIKASI PANGAN DI PASURUAN - Teguh Sarwo Aji; Novi Itsna Hidayati (Fakultas Pertanian Universitas Yudharta Pasuruan, 2017)
Until now it HAD a lot of institutions formed to participate in addressing the problem of providing food for the people. Starting from the institution handling food producers, marketing and distribution of food, food - re lated capital activities, food safety, food industry and other aspects of food. There was an institutional official government institutions, non - governmental pure, or which was the formal and informal collaboration between government and society. This stud y aims to identify local institutions that can be used to support the acceleration of food diversification program; analyze the role of local institutions based on their potential to support the acceleration of food diversification program in Pasuruan. In areas of research results show that there are 27 (nineteen) of local institutions that have the potential to support the acceleration of food diversification program. The institution consists of 4 institutional family welfare programs, 4 village consultati ve body, 4 institutional farmer groups, 4 institutional study, 3 institutional youth clubs and 4 farmers cooperative women. Based on the potential role of local institutions in supporting the acceleration of food diversification program in Pasuruan shows t hat institutional diversification potentially support the Food program was the first classification, namely the family welfare programs of Village Gerbo, village consultative body of Gerbo, village consultative body of Pucang Sari , family welfare programs of Pucang Sari, Farmers Group of Pucang Sari , family welfare programs of Village Suwayuwo, f armers g roup of Gerbo , Men Jam'iah Tahlil of Pucang Sari , Farmers Group of Suwahyuwo , family welfare programs of Pandaan Village, farmers cooperative women of G e rbo, farmers cooperative women of Pucang Sari , NU Moslem of Pandaan, NU Moslem of Suwayuwo